Super-resolved microstructure of pyrolyzing superlight ablators - Collin W. Foster; Sreevishnu Oruganti; Francesco Panerai (npj Materials Degradation)
Abstract The microstructural evolution of superlight ablators during pyrolysis was investigated using in situ X-ray micro-computed tomography and generative adversarial networks. Superlight ablators, a type of syntactic foam thermal protection materials, are commonly employed in the backshells of planetary entry probes. Synchrotron X-rays were used to resolve the material constituents during thermal degradation, including resin, silica microballoons, cork filler, refractory fibers, and voids. A super-resolution methodology was implemented, where high-resolution tomography scans were applied to denoise, segment and analyze lower-resolution in situ datasets that captured a large field of view. This multi-scale approach enabled the quantification of morphological and effective properties as a function of temperature during degradation, while also relating these changes to relevant decomposition chemistry. This study demonstrates a strategy for time-resolving rapid, multiphase decomposition events occurring under high-temperature test environments that mimic atmospheric entry.